Differential prognostic impact of stratified additional chromosome abnormalities on disease progression among Malaysian chronic myeloid leukemia patients undergoing treatment with imatinib mesylate - Siti Mariam, Ismail; Norhidayah, Ramli; Zulaikha, Abu Bakar; Nazihah, Mohd Yunus; Rosline, Hassan; Kausar, Ghazali Anis; Sarina, Sulong; Azlan, Husin; Ankathil, Ravindran (Frontiers in Oncology, 2022)
The emergence of additional chromosome abnormalities (ACAs) in chronic myeloid leukemia (CML) patients during treatment with a tyrosine kinase inhibitor (TKI) regime is generally associated with resistance to treatment and a sign of disease progression to accelerated phase or blast phase. We report the type, frequency, and differential prognostic impact of stratified ACAs with treatment response in 251 Malaysian CML patients undergoing TKI therapy. ACAs were observed in 40 patients (15.9%) of which 7 patients (17.5%) showed ACAs at time of initial diagnosis whereas 33 patients (82.5%) showed ACAs during the course of IM treatment. In order to assess the prognostic significance, we stratified the CML patients with ACAs into four groups, group 1 (+8/+Ph), group 2 (hypodiploidy), group 3 (structural/complex abnormalities); group 4 (high-risk complex abnormalities), and followed up the disease outcome of patients. Group 1 and group 2 relatively showed good prognosis while patients in group 3 and group 4 had progressed or transformed to AP or blast phase with a median survival rate of 12 months after progression. Novel ACAs consisting of rearrangements involving chromosome 11 and chromosome 12 were found to lead to myeloid BP while ACAs involving the deletion of 7q or monosomy 7 led toward a lymphoid blast phase. There was no evidence of group 2 abnormalities (hypodiploidy) contributing to disease progression. Compared to group 1 abnormalities, CML patients with group 3 and group 4 abnormalities showed a higher risk for disease progression. We conclude that the stratification based on individual ACAs has a differential prognostic impact and might be a potential novel risk predictive system to prognosticate and guide the treatment of CML patients at diagnosis and during treatment.